2021
DOI: 10.3390/ph14080742
|View full text |Cite
|
Sign up to set email alerts
|

Reynoutria Rhizomes as a Natural Source of SARS-CoV-2 Mpro Inhibitors–Molecular Docking and In Vitro Study

Abstract: More than a year has passed since the world began to fight the novel severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) responsible for the Coronavirus disease 2019 (COVID-19) pandemic, and still it spreads around the world, mutating at the same time. One of the sources of compounds with potential antiviral activity is Traditional Chinese Medicinal (TCM) plants used in China in the supportive treatment of COVID-19. Reynoutria japonica is important part of the Shu Feng Jie Du Granule/Capsule-TCM herba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 58 publications
1
26
0
Order By: Relevance
“…The report made by Nawrot-Hadzik et al ( 2021) showed significant effects of the butanol fractions from R. japonica and R. sachalinensis (especially vanicosides) on the inhibition of SARS-CoV-2 Mpro cells (7.877 g/mL, 4.031 g/mL, respectively at IC 50 ). However, these constituents may act in synergy with other compounds such as polymerized procyanidins that can also exhibit a strong inhibitory activity on the antiviral pathway, as suggested by previous authors [112].…”
Section: Anti-inflammatory and Antiviral Activitymentioning
confidence: 76%
See 1 more Smart Citation
“…The report made by Nawrot-Hadzik et al ( 2021) showed significant effects of the butanol fractions from R. japonica and R. sachalinensis (especially vanicosides) on the inhibition of SARS-CoV-2 Mpro cells (7.877 g/mL, 4.031 g/mL, respectively at IC 50 ). However, these constituents may act in synergy with other compounds such as polymerized procyanidins that can also exhibit a strong inhibitory activity on the antiviral pathway, as suggested by previous authors [112].…”
Section: Anti-inflammatory and Antiviral Activitymentioning
confidence: 76%
“…Recently, it became the spotlight of numerous studies, since its chemical composition has revealed promising therapeutic effects. Alcoholic, hydroalcoholic and water extracts from roots, rhizomes, and aerial parts (stems, leaves and flowers) have antibacterial activity [64,66,[93][94][95], antioxidant effects [44,58,66,[96][97][98][99][100][101][102][103][104][105], anticancer, antiproliferative and apoptotic properties [106][107][108], anti-inflammatory and antiviral activity [11,69,[109][110][111][112] and many other bioactive properties.…”
Section: Biological Activitiesmentioning
confidence: 99%
“…The main protease (Mpro, also called 3CLpro) is the nonstructural proteins of the virus, and inhibition of this enzyme could prevent the replication of the virus. Found that emodin revealed over 50% inhibition of SARS-CoV-2 Mpro, suggesting the beneficial effects of emodin on COVID-19 Nawrot-Hadzik et al (2021) . In order to improve the activity of emodin against human coronavirus NL63 (HCoV-NL63) and also to generate a set of initial SAR guidelines, Monika et al prepared emodin derivatives and found that halogenation of emodin can improve the antiviral activity of which.…”
Section: Antiviral Activity Of Emodinmentioning
confidence: 97%
“…Similarly, herbal medicines and their active ingredients have been shown to have significant antiviral effects ( Shao et al, 2021 ). There are some evidences (including in silico study and cell experiments) indicating that emodin might be effective therapy factor against SARS-CoV and COVID-19 ( Ho et al, 2007 ; Schwarz et al, 2011 ; Batista et al, 2019 ; Basu et al, 2020 ; Caruso et al, 2020 ; Boozari and Hosseinzadeh, 2021 ; Nawrot-Hadzik et al, 2021 ; Rolta et al, 2021 ), suggesting that it may be an effective new antiviral agent. Through collection and collation of related literature, we found that emodin also has good antiviral effects on other viruses, so the aim of this review is to collect and present the current experimental evidence for the antivirus efficacy and underlying mechanisms of emodin, with a view to informing the development of new antiviral drugs.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the ability of the theaflavin, a component of black tea, in inhibiting the RNA dependent RNA polymerase (RdRP) active site is well documented in many recent works on COVID-19 research [82]. Bioactive compounds like vanicoside B, resveratrol, epicatechin, emodin, piceid, epicatechin from various medicinal plants including Reynoutria japonica and Reynoutria sachalinensis was found effective against the main protease (Mpro) [83]. Nimbin, gedunin, and ginsenosides, important constituents of Panax ginseng, Zingiber officinale, Ocimum basilicum are potential inhibitors of the main protease required for viral replication process of coronaviruses [84].…”
Section: Encapsulation Replication Of the Virus And Viral Proteasementioning
confidence: 99%